2020
DOI: 10.12982/vis.2022.025
|View full text |Cite
|
Sign up to set email alerts
|

Surgical interventions of udder and teat affections in dairy cows

Abstract: Various udder and teat affections are most common in high yielding dairy cows which cause huge economic loss to the dairy sectors. This study focuses on the surgical affections of udder and teat in dairy cows to restore the moderate productive performance as well as the morphology of udder and teat through feasible surgical procedures. Fifty-four dairy cows with various surgical affections of udder and teat were experimented. The amounts of milk yield (litre/day), and the morphology of udder (symmetry of quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These lesions are primarily caused by environmental pathogens that are prevalent in the surroundings (Venkatesan et al, 2020 andPiccinini et al, 2012). Munif et al (2022) reported that among the udder affections in dairy cows, the prevalence of udder abscess was 9.26 percent and udder myiasis 11.11 percent. Abd-El-Hady, 2015 reported that among the udder affections in cattle, Gangrenous mastitis had a higher percentage (10%) followed by abscesses (5.83%), hematoma (5.6%), rupture of suspensory ligament (2.8%), and deep wounds (1.4%).…”
Section: Resultsmentioning
confidence: 99%
“…These lesions are primarily caused by environmental pathogens that are prevalent in the surroundings (Venkatesan et al, 2020 andPiccinini et al, 2012). Munif et al (2022) reported that among the udder affections in dairy cows, the prevalence of udder abscess was 9.26 percent and udder myiasis 11.11 percent. Abd-El-Hady, 2015 reported that among the udder affections in cattle, Gangrenous mastitis had a higher percentage (10%) followed by abscesses (5.83%), hematoma (5.6%), rupture of suspensory ligament (2.8%), and deep wounds (1.4%).…”
Section: Resultsmentioning
confidence: 99%